(untitled) (Journal of Environmental Bioremediation and Toxicology, 2023)
Biodegradation techniques employing microorganisms to remove industrial dyes are highly effective and environmentally friendly, and thus are being extensively explored. This research aims to evaluate the capacity of soil bacterium isolate a1 for degrading methylene blue (MB), specifically isolated from contaminated soil. The study was conducted in a laboratory setting using bacteria isolated from polluted soil. The focus was on assessing the influence of initial dye concentration and solution pH on the biodegradation process. The results demonstrated that an increase in the initial MB concentration from 50 to 400 mg/L resulted in a reduction in bacterial clearance efficiency from 90.41% to 71.28%. Additionally, the effect of pH on dye degradation was significant: raising the pH from 5 to 7 increased the percentage of methylene blue decolorization from 57.32% to 75.89%. However, further increasing the pH from 7 to 9 led to a decrease in decolorization efficiency from 75.89% to 46.17%. This study highlights the potential of soil bacterium isolate a1 for bioremediation of methylene blue in contaminated environments and underscores the importance of optimizing conditions such as dye concentration and pH to enhance biodegradation efficiency. The findings contribute valuable insights into the application of microbial bioremediation for industrial dye pollution.